Controlled syntheses of monodispersed metal oxide nanocrystals from bulk metal oxide materials. Issue 28 (3rd July 2020) - Zhao, Kaixuan; Yang, Zhijie; Wei, Huiying; Guo, Jinxin; Yang, Yanzhao; Wei, Jingjing
Abstract : High quality metal oxides nanocrystals are synthesized from bulk metal oxides in the presence of surfactants and high boiling point solvent. Abstract : The prevalent synthesis of colloidal metal oxide nanocrystals relies on the synthesis of various precursors, such as organometallic compounds, which are usually sensitive to moisture or oxygen and generally expensive. Based on the economic efficiency, the costs of the starting materials and synthetic process should be addressed. Herein, a general simple synthetic procedure from inexpensive and nontoxic precursors is developed. Under optimized reaction conditions, MnO nanocrystals are synthesized with commercially purchased bulk manganese oxides as starting materials, such as MnO, MnO2, and Mn3 O4 . The size and morphologies of nanoparticles are modulated by tuning the types and dosage of coating agents. Moreover, this synthetic strategy is further extended to other nanoparticles including Fe3 O4 nanocrystals and FeMnO x nanocrystals. Furthermore, Re doped MnO nanocrystals exhibiting fluorescence properties have been synthesized with this method, which endows the fluorescence properties to these oxide nanocrystals.